2017
DOI: 10.4269/ajtmh.16-0606
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics, Management, and Predictors of Outcome from Severe Community-Onset Staphylococcal Sepsis in Northeast Thailand: A Prospective Multicenter Study

Abstract: Staphylococcus aureus infection is a persistent threat in resource-restricted settings in southeast Asia but informative data about this disease remain limited. We analyzed characteristics, management, and predictors of outcome in severely septic patients with community-onset S. aureus infection in northeast Thailand. We performed a prospective, multicenter observational cohort study of community-onset S. aureus sepsis in four referral hospitals recruiting patients at least 14 years of age admitted between Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
2
6
0
4
Order By: Relevance
“…Our observations are consistent with other reports that high IL-8 is prognostic for all-cause mortality in SAB patients, 1,[5][6][7]19 including mortality in a cohort with IE caused by a variety of bacteria. 20 The prognostic value of IL-8 for mortality is not specific to SAB, as this has been observed across multiple sepsis cohorts including patients with both Gram-positive and Gramnegative bacterial infections.…”
Section: Clinical Endocarditissupporting
confidence: 93%
“…Our observations are consistent with other reports that high IL-8 is prognostic for all-cause mortality in SAB patients, 1,[5][6][7]19 including mortality in a cohort with IE caused by a variety of bacteria. 20 The prognostic value of IL-8 for mortality is not specific to SAB, as this has been observed across multiple sepsis cohorts including patients with both Gram-positive and Gramnegative bacterial infections.…”
Section: Clinical Endocarditissupporting
confidence: 93%
“…Among them, IL-6 is perhaps the best characterized. Several lines of evidence indicate that high IL-6 levels are correlated with bacterial sepsis, severe malaria, severe dengue, and increased risk of dengue mortality (39, 41, 44,46,48,50,[62][63][64][65][66][67][68]. A study in febrile adults reported IL-6 to be a good predictor analyte between non-survivors and survivors (54).…”
Section: Mediators Of Immune and Endothelial Activation As Prognosticmentioning
confidence: 99%
“…No entanto, isso muitas vezes não é possível, pois suas manifestações clínicas podem ser confundidas com quadros virais ou bacterianos inespecíficos ou outros processos não infecciosos e muitas vezes passam despercebidas. 7 Estudos demonstram que a rápida identificação da sepse, associada à terapêutica adequada, traz resultados favoráveis para o paciente. O uso de antimicrobianos específicos na primeira hora, logo após o diagnóstico, contribui substancialmente para um desfecho favorável ao paciente.…”
Section: Introductionunclassified
“…Mas, para que a identificação seja precoce e o tratamento adequado, é fundamental a aplicação efetiva dos protocolos de sepse e o treinamento da equipe multiprofissional, principalmente da equipe de enfermagem, para que os profissionais estejam aptos a identificar os sinais e manifestações clínicas da sepse. 7,8 Justificación y objetivos: La sepsis es un problema de salud públicaque genera impacto clínico y económico. El estudio pretende describir las características epidemiológicas y clínicas de lasepsis en un hospital público.…”
Section: Introductionunclassified